2019
DOI: 10.15376/biores.14.2.3266-3277
|View full text |Cite
|
Sign up to set email alerts
|

The influence of machining parameters on surface roughness of MDF in milling operation

Abstract: This paper examined the effect of machining parameters on surface roughness of medium density fiberboard (MDF) machined using a computer numerical control (CNC) router. The machining parameters such as spindle speed, feed rate, depth of cut, and tool diameter were examined for milling. The experiments were conducted at two levels of spindle speeds, four levels of feed rates, two levels of tool diameters, and two levels of axial depths of cut. The surface roughness values of MDF grooved by CNC were measured wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 26 publications
2
6
0
Order By: Relevance
“…It is seen that Ra value increases as the feed rate increases and it creates a statistically significant difference (P = 0,004). In the literature, it was stated that roughness values increase as a general tendency as the feed rate increases in the processing of wood and wood-based materials (Aykac and Sofuoglu 2021, Bal 2018, Bal and Akçakaya 2018, Davim et al 2009, Hazir et al 2018, Ilter et al 2002, Isleyen and Karamanoglu 2019, Karagoz 2010, Koc et al 2017, Pinkowski et al 2018, Sutcu and Karagoz 2012, Sofuoglu et al 2022. It seems that the data obtained in the study are compatible with the literature.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…It is seen that Ra value increases as the feed rate increases and it creates a statistically significant difference (P = 0,004). In the literature, it was stated that roughness values increase as a general tendency as the feed rate increases in the processing of wood and wood-based materials (Aykac and Sofuoglu 2021, Bal 2018, Bal and Akçakaya 2018, Davim et al 2009, Hazir et al 2018, Ilter et al 2002, Isleyen and Karamanoglu 2019, Karagoz 2010, Koc et al 2017, Pinkowski et al 2018, Sutcu and Karagoz 2012, Sofuoglu et al 2022. It seems that the data obtained in the study are compatible with the literature.…”
Section: Resultssupporting
confidence: 86%
“…While there was a slight decrease in the Ra value with the increase of speed from 12000 rpm to 15000 rpm, the decrease was higher with the increase of the speed from 15000 rpm to 18000 rpm. With the increase in the speed in rotary cutting cutters, roughness values decrease and smoother surfaces can be obtained (Aykac and Sofuoglu 2021, Davim et al 2009, Hazir et al 2018, Isleyen and Karamanoglu 2019, Karagoz 2010, Koc et al 2017, Sofuoglu 2015, Sutcu and Karagoz 2012, Sutcu and Karagoz 2013. It is seen that the data obtained in the study show similar trends with the literature.…”
Section: Resultssupporting
confidence: 80%
“…In another study [2], a feed rate of 2 m/min and a rotation speed of 18,000 rpm were found to be the optimal parameters for achieving superior surface quality in beech wood processing.…”
Section: Introductionmentioning
confidence: 96%
“…Many scientific works are focused on the determination of the influence of cutting parameters on the surface roughness of MDF in the machining process. However, the optimal parameters in these studies were generally found using the Taguchi method and statistical methods [31]. Artificial neural networks have found wide application in wood science, e.g., in recognizing wood species [32], wood-drying process [33], predicting some mechanical properties of wood [34], optimizing process parameters in the manufacturing process of wood products [35], classification of wood and veneer defects [36], calculation of thermal conductivity of wood [37], analysis of moisture in wood [38] and prediction of wood cracking resistance [39].…”
Section: Introductionmentioning
confidence: 99%